HUBUNGAN KEMATANGAN PRIBADI DENGAN PERSELINGKUHAN SUAMI - Putu Yunita Widhayanti; Fabiola Hendrati (Jurnal Psikologi Tabularasa, 2011)
Abstract Dishonesty is conduct within reason legitimate wife husband someone with other people, but not it official couple, its character is more to accomplish pleasing feel for agents. Dishonesty will make atmosphere in family becomes inharmonious. Harmonious one less deep family always becomes evoked problem deep nuptials, since will there are many loggerheaded and happening dispute.Variably if in family among husband and wife gets to interlace relationship with every consideration, therefore will most compose congruity in family. Utilised gets to interlace good relationship needed marks sense relationship among personal that warm. Having relationship self that warm with others constitutes one of criterion of ripe personality. Free variable in observational it is personal maturity and variable pending be husband dishonesty. Subject in observational it is husband at Wonosari's Orchard, which is 90 person . This research utilizes two scale, which is husband dishonesty scale that consisting of 60 item and personal maturity scales consisting of 63 item. Validity examination result utilizes formula product moment from Pearson points out 7 item that invalid and available 53 item that valid with ranging correlation coefficient among of 0,301 - 0,614, and for personal maturity scale points out 9 item invalid and available 54 item that valid or authentic with ranging correlation coefficient 0,301 0,784 . Result tests reliability husband dishonesty utilizes formula alpha cronbach pointing out correlation coefficient 0,900, and for personal maturity scale as big as 0,925. That thing points out both of variable measurement scale that reliable or having to mainstay. analysis result data by use of correlation product moment pearson point out that r = - 0,515 by r tables = -0,207 where if r computings -0,515 r table -0,207 its mean exist relationships that adequately strong among person maturity with husband dishonesty, one that matter personal maturity step-up will be followed by husband dishonesty decrease. Key word: Personal Maturity, Husband Dishonesty.